Assessing Knowledge of Systemic Lupus Erythematosus Among Patients and Caregivers Insights from a Qualitative Inquiry - Pratama, Mirza Zaka; Handono, Kusworini; Wahono, Cesarius Singgih; Rahman, Perdana Aditya; Wulandari, Dessy (Clinical and Research Journal in Internal Medicine, 2025)
Background: Systemic Lupus Erythematosus (SLE) is a complex autoimmune disease requiring comprehensive patient knowledge for effective management. However, gaps in understanding and educational challenges persist among patients and caregivers. Aim: This study aimed to explore the knowledge, perceptions, and educational needs of SLE patients and their caregivers through a qualitative approach. Methods: Semi-structured interviews and focus group discussions were conducted with 15 patients and 10 caregivers from rheumatology clinics at Saiful Anwar General Hospital. Participants were selected using purposive sampling. Data were analyzed using thematic analysis, identifying key themes related to understanding of SLE, sources of information, knowledge gaps, and educational needs. Results: Participants demonstrated a basic understanding of SLE, but significant misconceptions were identified, particularly regarding the disease's multi-systemic impact. Healthcare providers were the primary source of information, though time constraints limited the depth of understanding. Patients and caregivers frequently turned to online sources, encountering challenges in identifying reliable information. Complex medical terminology and the emotional burden of SLE management were significant barriers. There was a clear preference for simplified, visual educational materials and a need for ongoing, continuous education and support. Conclusion: The study highlights persistent knowledge gaps and the need for enhanced educational strategies tailored to the needs of SLE patients and caregivers. Improving communication, providing reliable resources, and offering continuous education could significantly improve disease management and patient outcomes.